Comparative Evaluation of the Immune Responses and Protection Engendered by LC16m8 and Dryvax Smallpox Vaccines in a Mouse Model - Meseda, Clement A. (American Society for Microbiology (ASM), 2009)
The immune response elicited by LC16m8, a candidate smallpox vaccine that was developed in Japan by cold selection during serial passage of the Lister vaccine virus in primary rabbit kidney cells, was compared to Dryvax in a mouse model. LC16m8 carries a mutation resulting in the truncation of the B5 protein, an important neutralizing target of the extracellular envelope form of vaccinia virus (EV). LC16m8 elicited a broad-spectrum immunoglobulin G (IgG) response that neutralized both EV and the intracellular mature form of vaccinia virus and provoked cell-mediated immune responses, including the activation of CD4(+) and CD8(+) cells, similarly to Dryvax. Mice inoculated with LC16m8 had detectable but low levels of anti-B5 IgG compared to Dryvax, but both Dryvax and LC16m8 sera neutralized vaccinia virus EV in vitro. A truncated B5 protein (∼8 kDa) was expressed abundantly in LC16m8-infected cells, and both murine immune sera and human vaccinia virus immunoglobulin recognized the truncated recombinant B5 protein in antigen-specific enzyme-linked immunosorbent assays. At a high-dose intranasal challenge (100 or 250 50% lethal doses), LC16m8 and Dryvax conferred similar levels of protection against vaccinia virus strain WR postvaccination. Taken together, the results extend our current understanding of the protective immune responses elicited by LC16m8 and indicate that the relative efficacy in a mouse model rivals that of previously licensed smallpox vaccines.